Esterase‐Activated Charge‐Reversal Polymer for Fibroblast‐Exempt Cancer Gene Therapy. Issue 48 (27th October 2016) - Qiu, Nasha; Liu, Xiangrui; Zhong, Yin; Zhou, Zhuxian; Piao, Ying; Miao, Lei; Zhang, Qianzhi; Tang, Jianbin; Huang, Leaf; Shen, Youqing
Abstract : Selective gene expression in tumors via responsive dissociation of polyplexes triggered by intracellular signals is demonstrated. An esterase‐responsive charge‐reversal polymer mediates selective gene expression in the cancer cells high in esterases over fibroblasts low in esterase activity. Its gene therapy with the TRAIL suicide gene effectively induces apoptosis of HeLa cells but does not activate fibroblasts to secrete WNT16B, enabling potent cancer gene therapy with few side effects.